Read Aloud Melalui Cerita Rakyat Dari Pendalungan - Dina Merdeka Citraningrum; Rofiatul Hima (Journal of Community Development, 2023)
Instilling moral values ​​through read aloud has the potential to be developed. This type of training serves to instill moral values ​​contained in the culture of pendalungan and provide knowledge about read aloud. Especially if the knowledge of the culture of pendalungan can be introduced directly to children. Mitra is the Almuna Creative community owned by Dania Puspitasari. The proposing team intends to collaborate to carry out read aloud training through folklore from Pendalungan. As for what partners are currently facing are: (a) partner's lack of understanding about guidance to parents in choosing the right books for children, (b) partner's lack of understanding about the importance of reading aloud through folklore from pendalungan, and (c) partner's lack of understanding about the folklore of pendalungan. Thus, based on the observations and presentations that have been described, the problems and solutions offered by the PKM Team can be obtained in the read aloud training activities through folklore from Pendalungan. The activities carried out in this PKM are given through the lecture method with a participatory learning approach with an emphasis on the principle of learning by doing. By understanding the presentation of this PKM activity, participants can be moved in conveying messages through folklore from Pendalungan. The PKM team gave presentations on: (a) guidance to parents in choosing the right books for children, (b) the importance of reading aloud through folklore from pendalungan, and (c) folklore from pendalungan. The results obtained during the activity included: a) PKM participants had guidelines in choosing the right books for children, (b) PKM participants had the ability to convey messages through reading aloud strategies based on fun folklore from pendalungan, (c) PKM participants had understanding of folklore from pendalungan as a strategy for instilling moral values.